PERAN DAN FUNGSI OTORITAS JASA KEUANGAN (OJK) DALAM SISTEM KEUANGAN DI INDONESIA (PERSPEKTIF HUKUM ISLAM) - Muhammad Fakhri Amir (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2020)
The aims of this study are to find out how the role and function of the Otoritas Jasa Keuangan (OJK) in the financial system in Indonesia, and how the Islamic inspection regarding the existence of OJK in the financial system. This study is a library research that tries to utilize data and references which are relevant to the discussion on this study, then it is followed by explanation, analysis, and conclusion that used the Islamic law approach. Based on the results of this study, OJK has the functions, duties, and authority in regulating the regulatory system and conducting oversight of financial service activities. In Islam, the existence of OJK and its role and function are legal, because OJK is an institution in the financial system which aims to achieve benefit and reject damage and harm that is included in the al-dharuriyat al-khamsa part and it is closer to maintaining assets (hifz al-maal).